2007
DOI: 10.1016/s1726-4901(08)70044-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glyburide—Metformin Combination Tablet in Patients with Type 2 Diabetes

Abstract: Both glyburide/metformin 2.5 mg/500 mg and glyburide/metformin 5.0 mg/500 mg combination therapy were efficacious and well tolerated in the treatment of Chinese patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…e bulk density was between 0.41 ± 0.00 and 0.59 ± 0.02 g/mL and tapped density between 0.47 ± 0.00 and 0.63 ± 0.00 g/mL. All formulations had Hausner's ratio less 4 Advances in Pharmacological and Pharmaceutical Sciences than 1.18, Carr's index between 6.30% ± 0.60% and 15.78% ± 0.20%, and angle of repose in the range of 25.00 ± 1.10°to 27.00 ± 2.30°. According to these results, granules from all batches had good to excellent flow properties [14].…”
Section: Granule and Tablet Characteristics Of The Preliminary Formulmentioning
confidence: 97%
See 1 more Smart Citation
“…e bulk density was between 0.41 ± 0.00 and 0.59 ± 0.02 g/mL and tapped density between 0.47 ± 0.00 and 0.63 ± 0.00 g/mL. All formulations had Hausner's ratio less 4 Advances in Pharmacological and Pharmaceutical Sciences than 1.18, Carr's index between 6.30% ± 0.60% and 15.78% ± 0.20%, and angle of repose in the range of 25.00 ± 1.10°to 27.00 ± 2.30°. According to these results, granules from all batches had good to excellent flow properties [14].…”
Section: Granule and Tablet Characteristics Of The Preliminary Formulmentioning
confidence: 97%
“…Health care providers usually prescribe metformin and glibenclamide together as a first-line therapy during the management of type II DM patients. is combination is also used when a monotherapy of each drug failed to effectively manage the case [4,5]. However, the use of two or more separate tablets for the management of DM has exposed patients to pill burden which often leads to poor treatment adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin suppresses hepatic gluconeogenesis and increases peripheral tissue insulin sensitivity (7,8). Clinical studies have demonstrated that metformin-sulfonylurea combinations produce greater improvements in glycemic control than either sulfonylurea or metformin monotherapies (9)(10)(11)(12). However, there are no animal studies that demonstrate a synergic hypoglycemic effect between metformin and sulfonylureas.…”
mentioning
confidence: 99%
“…An incidence of mild hypoglycemia was recorded in the FDC group.González-Ortiz et al 14 (2008)N = 152, randomized, double-blind, multicenter, 12 monthsGlimepiride (1 g) + metformin (500 mg), 2 tablets QD as FDCGlimepiride and metformin group showed a greater reduction in FPG, PPBS, and HbA 1c compared with glibenclamide and metforminMild to moderate hypoglycemia was noted in glimepiride group, which was lower in incidence compared with glibenclamideGoldstein et al 12 (2007)N = 1091, randomized, double-blind, parallel group, 24 weeksSitagliptin (50 mg) + metformin (500, 1000 mg)There was a significant reduction in HbA 1c and FPGThe incidence of hypoglycemia and gastrointestinal side effects was higher in the high-dose metformin group. Treatment was generally well tolerated.BID as FDCChien et al 16 (2007)N = 100, multicenter, randomized, double-blind, parallel group, 16 weeksGlyburide (2.5, 5 mg) + metformin (500 mg) as FDCFDC had a greater reduction in FPG, HbA 1c compared with monotherapy. The FDC also improved adherence in patients.The combination was efficacious and well tolerated, and the incidence of gastrointestinal ADRs was lower compared with monotherapy.Bailey et al 10 (2005)N = 568, 24 weeks, multicenter, randomized, double blind, parallel group studyRosiglitazone 4 and 8 mg; metformin 2 g increased to 3 g at the time of treatmentThe FDC showed a significant improvement in HbA 1c , FPG values compared with patients treated with a high dose of metformin, ie, 3 g/dIt was well tolerated with a lower incidence of diarrhea, abdominal pain compared with the metformin group.

ADRs = adverse drug reactions; FBG = fasting blood glucose; FBS = fasting blood sugar; FDC, fixed-dose combination; PPBS = post prandial blood sugar; PPG, postprandial glucose; TDS = three times a day; UTI, urinary tract infection.

…”
Section: Resultsmentioning
confidence: 99%
“…However, there are some limitations for FDCs such as difficulty in dose titration and stability problems between the drugs leading to incompatibilities. Study design, intervention, outcomes, and safety of FDC use in T2DM was shown in Table II,3, 5, 10, 12, 14, 16, 18, 23, 30, 31 and bioavailability of FDCs is shown in Table III 33, 34Table IIStudies reporting the use of FDCs in T2DM patients.AuthorType of studyInterventionOutcomesSafetyVed et al 3 (2016)N = 400, open label, prospective, nonrandomized, multicenter, observational study, 3 monthsVildagliptin (50 mg) + metformin (500, 850, 1000 mg) as FDCMean value for FBG, PPG, and HbA 1c were significantly reduced after treatmentNot reported in this studyRombopoulos et al 18 (2014)N = 366, multicenter, observational study, 26 weeksVildagliptin (50 mg) + metformin (850 mg) as FDCIt resulted in a greater reduction in HbA 1c compared with free-dose combination; the patients with FDC were more compliant than with free doseNot reported in this studyLewin et al 23 (2013)N = 273, phase III, randomized, double- blind, parallel group, 52 weeksEmpagliflozin (25, 10 mg) + linagliptin (5 mg) as FDCReduction in HbA 1c was significantly greater with FDC compared with individual componentsThe incidence of ADRs such as UTI, genital infection, were more with empagliflozin 25 mg + linagliptin 10 mg compared with the other compared with the other group but were tolerable with medicationWang et al 5 (2012)N = 233, randomized, double-blind, parallel group, 16 weeksAcarbose (50 mg) + metformin (500 mg) TDS as FDCThe combination significantly reduced FBS, HbA 1c , and PPPG with superior efficacy compared with monotherapyNo hypoglycemia was reported.…”
Section: Resultsmentioning
confidence: 99%